Development of Traditional Game-Based Physical Education Learning Against Anti-Bullying Attitudes in Schools - Isnaini, Lalu Moh Yudha; Saputra, Lulut Gilang; Rusdiyanto , Rajip Mustafillah; Nor, Mohad Anizu Mohd (Jurnal Porkes, 2025)
Bullying remains a persistent problem in schools, negatively impacting students' psychological and social well-being. While physical education has the potential to foster positive character traits, the use of traditional games to promote anti-bullying attitudes is still underexplored, and physical education teachers do not yet have a structured model for implementing such approaches effectively. This research utilized a Research and Development (R&D) approach conducted in Lombok, Indonesia. The development procedure included needs analysis, model design, expert validation, limited field trial, extensive field trial, and iterative revisions. A limited trial was carried out with 30 elementary school students, while the extensive trial involved 120 students. Data were collected through observations, interviews, and questionnaires. The developed model, based on traditional games such as gobak sodor, fort and engklek, was validated by experts and successfully implemented in selected schools. Results indicated significant improvements in students’ empathy and mutual respect, accompanied by a noticeable reduction in aggressive behavior. Teachers reported high acceptance and ease of application. The study concludes that integrating traditional games into physical education lessons can foster anti-bullying attitudes in students. This culturally grounded, character-focused model enhances social-emotional learning and provides practical tools for educators to address bullying through inclusive and meaningful physical activity.